2019
DOI: 10.1021/acs.iecr.9b03975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morphology and Surface Properties of Copper Oxide on the Removal of Hydrogen Sulfide from Gaseous Streams

Abstract: This work studies the effects of microscopic shape, crystallinity, and purity for the chemical reaction of CuO nanoparticles with hydrogen sulfide (H 2 S) to form copper sulfide. Several CuO nanomaterials were prepared via various synthesis techniques, including sol-gel, precipitation, hydrothermal synthesis in the presence of a polymer/surfactant, hydrolysis, and electrospinning, using different copper precursors (nitrate and acetate) and thermal treatment conditions (623 to 1023 K). The synthesized materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 53 publications
5
32
0
1
Order By: Relevance
“…La was chosen because of its large cationic radius (R La /R Cu ≈ 1.5) compared to the more commonly studied additives such as zinc, nickel and cobalt (R x /R Cu ≈ 1.0). This difference in cationic radius is expected to introduce disruptions to the CuO lattice, 23,26 which would cause the formation of O‐atoms that are more reactive with adsorbed surface species, 27 similar to previous studies that have found similar disruptions to the ([Mn, Zn]Fe 2 O 4 , ZnMnO 3 ) lattice by the presence of Mn increases the sulfur sorption of a Fe‐Mn‐Zn‐Ti mixed oxide 28 …”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…La was chosen because of its large cationic radius (R La /R Cu ≈ 1.5) compared to the more commonly studied additives such as zinc, nickel and cobalt (R x /R Cu ≈ 1.0). This difference in cationic radius is expected to introduce disruptions to the CuO lattice, 23,26 which would cause the formation of O‐atoms that are more reactive with adsorbed surface species, 27 similar to previous studies that have found similar disruptions to the ([Mn, Zn]Fe 2 O 4 , ZnMnO 3 ) lattice by the presence of Mn increases the sulfur sorption of a Fe‐Mn‐Zn‐Ti mixed oxide 28 …”
Section: Introductionsupporting
confidence: 75%
“…In summary, the laboratory‐based characterization showed that CuO‐La‐2, compared to CuO‐La‐1, features larger crystals but has a higher inclusion of La throughout the CuO phase. These results suggest that the improvement in sulfur uptake by CuO‐La‐2, compared to CuO‐La‐1, is related to a higher concentration of La dopants which induce lattice expansion and strain, which have been previously identified as a means to increase H 2 S capacity of CuO adsorbents 22,23,25 …”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…As in commercial products such as SulfaTreat ® [ 38 ], copper (II) oxide (CuO) was added to Fe 2 O 3 in some samples during the preparation of pellets to enhance the adsorption capacity of the solid phase [ 39 ]. The copper oxide was selected among other possible metal oxides as its sorbent properties towards H 2 S are well known in the literature [ 40 ]. Three different kinds of pellets were produced containing 5%, 10% and 15% w / w CuO in the mixture, respectively.…”
Section: Methodsmentioning
confidence: 99%